2016
DOI: 10.4067/s0718-07642016000600007
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de Temperatura, pH, Concentración de Sustrato y Tipo de Enzima en la Hidrólisis Enzimática de Vísceras de Tilapia Roja (Oreochromis spp.)

Abstract: ResumenSe prepararon hidrolizados de proteína a partir de vísceras de Tilapia roja (Oreochromis spp.), una importante especie de pescado de gran producción en Colombia. En la hidrólisis se evaluaron tres enzimas diferentes (Alcalase, Neutrase y Flavourzyme) para establecer con cuál de ellas se obtendría el mayor grado de hidrólisis (GH). Se utilizó el método del pH-stat y en cada enzima se aplicó un diseño factorial 2 2 para evaluar el efecto de la temperatura y el pH, sobre el GH. Se alcanzaron valores máximo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
5
0
2
Order By: Relevance
“…However, it can be observed that there is a significant difference (p≤0.05) for a pH of 6.33, these results suggest that the pH has an important effect at the time of hydrolyzing. These results agree with the studies carried out by Baez-Suarez et al (2016) This scientific publication in digital format is a continuation of the Printed Review: Legal Deposit pp 196802ZU42, ISSN 0378-7818.…”
Section: Protein Concentration and Hydrolysis Approximationsupporting
confidence: 90%
“…However, it can be observed that there is a significant difference (p≤0.05) for a pH of 6.33, these results suggest that the pH has an important effect at the time of hydrolyzing. These results agree with the studies carried out by Baez-Suarez et al (2016) This scientific publication in digital format is a continuation of the Printed Review: Legal Deposit pp 196802ZU42, ISSN 0378-7818.…”
Section: Protein Concentration and Hydrolysis Approximationsupporting
confidence: 90%
“…En las vísceras de tilapia roja (Oreochromis sp.) el contenido de aceite oscila alrededor 28% (Baez et al, 2016), por lo que su recuperación constituye un aspecto relevante, ya que este residuo usualmente es descartado al ambiente generando además importantes impactos negativos (Martinez-Álvarez, 2011).…”
Section: Introductionunclassified
“…For bromelain, only the amount of substrate was significant. As mentioned in the previous section, a change in the amount of substrate can positively or negatively affect the enzyme, even inhibiting it if the substrate exceeds the amount to be applied [30]. It is important to highlight that there are few reports that exist in relation to cooked shrimp by-products; Wan et al [31] identified and characterized an antioxidant peptide from chicken feather keratin hydrolyzates, reporting 80% inhibition by the ABTS method using Bacillus subtilis for hydrolysis, employing 72 h and 37 • C with a concentration of these by-products of ~0.35 mg/mL.…”
Section: Amino Acid Profile By Gc-ms Under Optimal Hydrolysis Conditionsmentioning
confidence: 93%